Comparative Genomics Reveals Ancient and Unique Pathogenicity Features in Australian Fusarium oxysporum f. sp. vasinfectum - Angel David Popa-Baez; Linda J. Smith; Warwick N. Stiller; Melanie Soliveres; Gunjan Pandey; Christopher A. Saski; Don C. Jones; Iain W. Wilson (Journal of Fungi, 2025)
Fusarium oxysporum f. sp. vasinfectum (Fov) is a devastating cotton pathogen. Australian Fov strains are distinguished by their ability to infect plants without nematode interaction and are genetically distinct from global Fov, classified into two vegetative compatibility groups (VCG-01111 and VCG-01112). Here, we present chromosome-level genome assemblies of a historical isolate for each Australian Fov VCG. The end-to-end gapless genome assemblies demonstrate high contiguity and completeness, with 97.7% BUSCO completeness for both isolates. Phylogenetic analysis indicates that the Australian Fov lineages diverged from other known Fov genomes over 3.6 million years ago, while VCG-01111 and VCG-01112 separated approximately 1.1 million years ago. Comparative genomics analysis identified four accessory chromosomes unique to the Australian isolates. Functional annotations revealed 14,495 and 15,342 genes in VCG-01111 and VCG-01112, respectively, with accessory chromosomes containing significantly fewer genes than core chromosomes. Ortholog analysis uncovered unique gene clusters enriched in key metabolic pathways, pathogenicity, and cell division processes. Additionally, we identified several novel lineage-specific peptides unique to each Australian isolate. This comprehensive genomic characterization provides the first insights into the unique evolutionary history of Australian Fov, distinguishing them from global Fov races. Our findings lay the foundation for understanding the genetic factors underlying their exceptional virulence, which makes Australian Fov among the most aggressive cotton pathogens worldwide.